Semiotic Analysis of The Meaning in The Lyrics of The Song "Manusia Kuat" by Tulus - I Gede Dwi Setiadi (PRAGMATICA : Journal of Linguistics and Literature, 2025)
This study examines the meaning of motivation in the lyrics of the song "Manusia Kuat" by Tulus using a semiotic analysis approach. The focus of the research is to identify and analyze the signs that represent the concept of motivation in the lyrics. Using the framework of the semiotic theory of Charles Sanders Peirce, this study analyses icons, indexes, and symbols in song lyrics. The research method used is descriptive qualitative with semiotic analysis techniques. The results of the study show that the lyrics of the song "Manusia Kuat" contain various signs that represent the concept of strength, resilience, and self-motivation in facing life's challenges. These signs form a motivational narrative that reflects contemporary and universal Indonesian cultural values of struggle and perseverance. This research contributes to the understanding of how popular musical works can function as a medium to convey motivational messages through semiotic constructions.